Disability–free survival after coronary artery bypass grafting in women and men with heart failure. Issue 2 (5th November 2018) - Sun, Louise Y; Tu, Jack V; Lee, Douglas S; Beanlands, Rob S; Ruel, Marc; Austin, Peter C; Eddeen, Anan Bader; Liu, Peter P
Abstract : Objective: Heart failure (HF) impairs survival post coronary artery bypass grafting (CABG), but little is known about the postoperative quality of life (QoL) in patients with HF. We derived a patient-centred QoL surrogate and assessed the impact of different HF subtypes on this surrogate in the year post-CABG. Methods: We surveyed 3112 cardiovascular patients to derive a patient-centred disability outcome and studied this outcome in a population-based cohort. We defined preserved ejection fraction as ≥50% and reduced ejection fraction as <50%. The primary outcome was disability, defined according to compiled patient-derived values. The secondary outcomes consisted of each individual component of disability, and death. The incidence of disability was calculated using cumulative incidence functions, with death as a competing risk. We identified predictors of disability using cause-specific hazard models. Results: Patient-derived disability outcome consisted of stroke, nursing home admission and recurrent hospitalisations. When applied to 40 083 CABG patients (20.6% women), the incidence of disability was 5.4% while the incidence of death was 3.7% in the year post-CABG. Female sex was associated with an adjusted HR of 1.25 (95% CI 1.13 to 1.37) for disability. Women with HF with preserved ejection fraction had an adjusted HR of 1.73 (95% CI 1.52 to 1.98) for disability. Conclusions: Disability was a more frequent complication than death in the year post-CABG. Women experienced higher burden of disability than men, and female sex and the presence of HF were important disability risk factors. Efforts should be dedicated to disability risk prediction to enable patient-centred operative decision-making and to developing sex-specific treatment strategies to improve outcomes.